Wastewater Treatment in the Brewing Industry Using Chlorella vulgaris - Wichanuchit, Worakai; Pung, Thitiya; Panich-pat, Thanawan (Journal of Food Health and Bioenvironmental Science, 2023)
We studied the wastewater treatment efficiency of brewing industry effluents using the growth and biomass of the microalgae Chlorella vulgaris. Wastewater treated at% concentrations of 0, 20, 40, 60, 80 and 100 was examined and evaluated using the parameters of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Suspended Solids (SS), Phosphate (PO43-) as ascorbic acid), TKN Nitrogen (Total Kjeldahl Nitrogen) and Total Dissolved Solids (TDS). Treatment reductions noted were 52.48% BOD, 52.42% COD, 79.12% SS, 40.82% Phosphate, 98.72% TKN and 43.96% TDS. During treatment, fats and oils measured as Oil and Grease (OG) increased to a maximum of 70.55% and Chlorella vulgaris at day 5 had the highest growth at 7.8x105 cells per mL cultured in wastewater in a concentration of 100%. A maximum of 0.1541 g/L of dry biomass was obtained in 80% wastewater concentration. The autoclave method was the best method to extract oil by Chlorella vulgaris with an extraction value at 6.3%.